Analysis Of Tpack (Technological Pedagogical And Content Knowledge) In Improving The Digital Competence Of Physical Education Teachers In South Tangerang City - Achanul Fikri; Akhmad Sobarna; Muchamad Ishak (UNIB Press, 2025)
The purpose of this study is to analyze TPACK in improving digital competence (skills, attitudes, and knowledge) of Physical Education Teachers. This study uses qualitative research. The research sample consisted of 10 physical education teachers who had completed PPG. The instrument used in this study was an interview. The results of this study are that teachers in Ciputat District have implemented hardware and software used in the teaching and learning process to provide an understanding of physical education material, good teacher delivery in facilitating students during the learning process, and supplemented with examples that can be easily understood by students, understanding and mastery of the material that must be possessed by a teacher. for teachers in Ciputat District, especially physical education teachers, various obstacles that occur to teachers in Ciputat District, one of which is the lack of use of TPACK by teachers, and the selection of appropriate teaching media to minimize TPACK learning in class by teachers.